Rice leaf growth and water potential are resilient to evaporative demand and soil water deficit once the effects of root system are neutralized - Parent, Boris; Suard, Benoît; Serraj, Rachid; Tardieu, François (Wiley, 2010)
Rice is known to be sensitive to soil water deficit and evaporative demand, with a greatest sensitivity of lowland‐adapted genotypes. We have analysed the responses of plant water relations and of leaf elongation rate (LER) to soil water status and evaporative demand in seven rice genotypes belonging to different species, subspecies, either upland‐ or lowland‐adapted. In the considered range of soil water potential (0 to −0.6 MPa), stomatal conductance was controlled in such a way that the daytime leaf water potential was similar in well‐watered, droughted or flooded conditions (isohydric behaviour). A low sensitivity of LER to evaporative demand was observed in the same three conditions, with small differences between genotypes and lower sensitivity than in maize. The sensitivity of LER to soil water deficit was similar to that of maize. A tendency towards lower sensitivities was observed in upland than lowland genotypes but with smaller differences than expected. We conclude that leaf water status and leaf elongation of rice are not particularly sensitive to water deficit. The main origin of drought sensitivity in rice may be its poor root system, whose effect was alleviated in the study presented here by growing plants in pots whose soil was entirely colonized by roots of all genotypes.